Comparing qSMI and qCEUS for assessing vascularization in uterine cervical cancer: operable versus non-operable group - Zhu, Yi; Li, Yanjie; Tang, Yixin; Zhang, Jie; Jia, Shijun; Jiang, Zhuolin; Luo, Xinyi; Ishikawa, Mitsuya; Kato, Tomoyasu (Frontiers in Oncology, 2024)
Objective: The present study aimed to compare the effectiveness and reliability of quantified superb microvascular imaging (qSMI) and quantified contrast-enhanced ultrasonography (qCEUS) in assessing vascularization in both operable and non-operable uterine cervical cancer.A case-control study included 64 patients with pathology-proven and untreated cervical cancer, who underwent transvaginal ultrasonography combined with qSMI and qCEUS between January 2022 and June 2023. SMI results were quantified as the vascular index (VI), which were compared to 12 quantitative parameters of CEUS calculated with timeintensity curves (TIC).Results: According to FIGO staging and different treatment regimens, 64 patients with cervical cancer were divided into operable group (IA IIA, n = 19) and non-operable group (IIB IV, n = 45). In comparison to the operable group, the non-operable group showed significantly higher values in VI, peak intensity (PI), area under the curve (AUC), wash-in area (iAUC), wash-out area (oAUC), wash-in rate (WiR), mean intensity (Mean Int), and standard deviation (STD) (all P < 0.05). VI demonstrated strong correlations with CEUS parameters, notably PI (r = 0.854, P < 0.001) and AUC (r = 0.635, P < 0.001). Furthermore, VI showed a better predictive performance for treatment-group assignment than qCEUS parameters, with an 80.7% accuracy, 64.4% sensitivity and 89.5% specificity.Both qSMI and qCEUS exhibit significant and comparable utility in detecting microvascular hyperplasia and predicting treatment-group assignments in cervical cancer. Furthermore, qSMI may offer added convenience in implementation.